Early Planet Formation in Embedded Disks (eDisk). XXI. Limited Role of Streamers in Mass Supply to the Disk in the Class 0 Protostar IRAS 16544-1604 - Miyu Kido; Hsi-Wei Yen; Jinshi Sai; Shigehisa Takakuwa; Nagayoshi Ohashi; Yuri Aikawa; Yusuke Aso; Christian Flores; Ilseung Han; Patrick M. Koch; Woojin Kwon; Jeong-Eun Lee; et al. (The Astrophysical Journal)
Asymmetric and narrow infalling structures, often called streamers, have been observed in several Class 0/I protostars, which is not expected in the classical star formation picture. Their origin and impact on the disk formation remain observationally unclear. By combining data from the James Clerk Maxwell Telescope (JCMT) and Atacama Large Millimeter/submillimeter Array (ALMA), we investigate the physical properties of the streamers and parental dense core in the Class 0 protostar, IRAS 16544–1604. Three prominent streamers associated to the disk with lengths between 2800 and 5800 au are identified on the northern side of the protostar in the C ^18 O emission. Their mass and mass infalling rates are estimated to be in the range of (1–4) × 10 ^−3 M _⊙ and (1–5) × 10 ^−8 M _⊙ yr ^−1 , respectively. Infall signatures are also observed in the more diffuse extended protostellar envelope observed with the ALMA from the comparison to the infalling and rotating envelope model. The parental dense core detected by the JCMT observation has a mass of ∼0.5 M _⊙ , a subsonic to transonic turbulence of ${ \mathcal M }$  =  0.8–1.1, and a mass-to-flux ratio of 2–6. Our results show that the streamers in IRAS 16544–1604 only possess 2% of the entire dense core mass and contribute less than 10% of the mass infalling rate of the protostellar envelope. Therefore, the streamers in IRAS 16544–1604 play a minor role in the mass accretion process onto the disk, in contrast to those streamers observed in other sources and those formed in numerical simulations of collapsing dense cores with similar turbulence and magnetic field strengths.